BIOLOGICAL ASPECT AND ABUNDANCE OF TRITON EPAULETTE SHARK (Hemiscyllium henryi) ENDEMIC TO TRITON BAY, KAIMANA, WEST PAPUA - Prehadi, Prehadi; Kintani, Novia Indah; Sombo, Hendrik; Fahlevi, Arief Reza; Junaedy, Ahmad; Muttaqin, Ahmad Sabilul; Raweyai, Oktofianus Obaja; Kusumarani, Dheni; Raunsai, Jhoni Elias; Fenetiruma, Syamsudin; Malaihollo, Jantje Jacobus; Herettrenggi, Rosa; Widiarto, Santoso Budi; Subhan, Beginer; Ayuningrum, Diah (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2024)
Walking shark is one of elasmobranch that has been protected by the government of the Republic of Indonesia and can be found in the eastern seawaters of Indonesia. There are six species of walking shark, one of it is Triton Bay Epaulette Shark (Hemiscyllium henryi) which is endemic to the coastal waters of Kaimana. There are still lack of information regarding biology abundance and population of H. henryi, therefore it is necessary to do a study related to this species. This study aims to determine individual information and abundance of H. Henryi in Kaimana coastal waters during the observation in 2022 and 2023 based on density value and potential area. The method used is a census based on the Global Positioning System, through snorkeling and walking along the coastline, as well as observations of total length, wet weight, and sex in H. henryi which encountered during census. The total census track is 5.783 meters with a sweep of 2,46 Ha monitoring area. The density or abundance of H. henryi in 2022 is 1,2 ind/Ha and in 2023 is 2,4 ind/Ha. Total length of H. henryi ranged between 55–88 cm (Mean 70,6 cm ± SD 12,29). The length and weight relationship obtained W=0,0004L3,4343 with R2 value of 0,9526. The abundance trend of H. henryi at the coastal waters of Kaimana in the last two years has multipled by 2 times based on density value determining after being designated as a fully protected fish species.